2009
DOI: 10.2166/aqua.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron on nitrification in full-scale drinking water trickling filters

Abstract: In the production of drinking water from groundwater, iron removal in filters may interfere with nitrification. Microbiai nitrification might decline because of irreversible accumulation of iron deposits in pores and on filter material. This paper shows the successful application of two experimental techniques applied at a full-scale water treatment plant in the Netherlands to maintain sustainable nitrification. Filter performances were evaluated by measurements of ammonium in the filter effluent, accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…The higher number of AOP in water sampled after tower aeration and pellet softening than in water from the first rapid sand filter at plant B implies that biological nitrification is limited in the first rapid sand filter. The raw water of plant B contains high concentrations of DOC, methane, iron, and manganese, which might limit nitrification during biological filtration (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…The higher number of AOP in water sampled after tower aeration and pellet softening than in water from the first rapid sand filter at plant B implies that biological nitrification is limited in the first rapid sand filter. The raw water of plant B contains high concentrations of DOC, methane, iron, and manganese, which might limit nitrification during biological filtration (2,9).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the time required for a biofilter to reach compliance is usually a few months when using inherent inoculation (Štembal et al, 2004). Possible reasons for this lengthy start-up period include low water temperatures, low availability of nutrients, weak inoculation or other factors (de Vet et al, 2012). A comparison of the length of the start-up period from various studies in the literature is virtually futile, largely due to diverging experimental conditions and focus.…”
Section: Introductionmentioning
confidence: 99%
“…Subsurface aeration is a mild form of in situ iron removal (Braester and Martinell, 1988). The drinking water company Oasen in the Netherlands applies this technique not for the purpose of in situ iron removal, but for the enhancement of nitrification in the water treatment plant (WTP; de Vet et al, 2009a). In this technique, limited amounts of well‐aerated tap water are periodically injected back into the anaerobic groundwater aquifer, which contains ferrous iron, in between longer periods of groundwater abstraction.…”
Section: Introductionmentioning
confidence: 99%